1982
DOI: 10.1111/j.1600-0447.1982.tb00928.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre placebo‐controlled trial comparing the efficacy of mianserin and chlordiazepoxide in general practice patients with primary anxiety

Abstract: In a double-blind multicentre trial in general practice, 144 patients with primary anxiety received daily treatment with mianserin or chlordiazepoxide, 30-60 mg, or placebo. There were no statistically significant differences in efficacy between the three treatments in the 106 patients who completed the 6-week trial. However, there was a substantial trend in favour of mianserin (P = 0.1), but not chlordiazepoxide, over placebo as assessed by the difference in overall improvement on the Hamilton Anxiety Scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It has been demonstrated repeatedly that mianserin has clinically significant anxiolytic effects at least equal to those of the benzodiazepines [Murphy 1978;Bjertnaes et al, 1982;Kahn et al, 1986;Khan et al, 1983;Granier et al, 1985;Sorensen et al, 19851, although the anxiolytic effects of mianserin have only been reported once prior to this study [Bodnoff et al, 19891 in animals. A possible explanation is that, prior to 1989, mianserin was only tested acutely, where it did not appear to produce any systematic effect (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…It has been demonstrated repeatedly that mianserin has clinically significant anxiolytic effects at least equal to those of the benzodiazepines [Murphy 1978;Bjertnaes et al, 1982;Kahn et al, 1986;Khan et al, 1983;Granier et al, 1985;Sorensen et al, 19851, although the anxiolytic effects of mianserin have only been reported once prior to this study [Bodnoff et al, 19891 in animals. A possible explanation is that, prior to 1989, mianserin was only tested acutely, where it did not appear to produce any systematic effect (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…In a subgroup of the patients, who were reintroduced to the pharmacological treatment, body weight increased by 3 to 12 kg (65). However, in other larger human studies comparing various anxiolytics with other psychotropic drugs in subjects without severe physical handicaps, weight gain has not been reported as a side effect (66,67). Weight loss has also been described (68).…”
Section: Antianxiety Drugsmentioning
confidence: 99%
“…Thus, mirtazepine alone among the newer generation of antidepressants has been most commonly associated with weight gain [113] and is the only one among the serotonin-selective reuptake inhibitors (SSRI's), dual 5-HT/NE reuptake inhibitors (SNRI's) and others (including bupropione and nefazadone) to have high H1-receptor affinity ( Table 1). Finally, mianserin, an older antidepressant with a novel mechanism of action which causes weight gain [117], also has a pharmacological profile predictive of weight gain in humans. two tricyclic antidepressant medications long associated with weight gain-imipramine [114,115] and amitriptyline [116]have a pharmacological profile predictive of weight gain.…”
Section: Drug-induced Weight Gain: Validation Of Histamine Receptors mentioning
confidence: 99%